Identification of Underlying Inflammation in Vogt–Koyanagi–Harada Disease with Sunset Glow Fundus by Multiple Analyses. (3rd October 2019) - Murata, Toshihiko; Sako, Nanae; Takayama, Kei; Harimoto, Kozo; Kanda, Koji; Herbort, Carl P.; Takeuchi, Masaru
Abstract : Purpose . To evaluate underlying subclinical ocular inflammation in Vogt–Koyanagi–Harada (VKH) disease with sunset glow fundus (SGF) by multiple analyses. Study Design . Retrospective observational study. Methods . Clinical records of 34 eyes of 17 VKH patients with SGF in whom laser flare photometry (LFP), enhanced depth imaging optical coherence tomography (EDI-OCT), and indocyanine green angiography (ICGA) were performed on the same day were reviewed. The mean age was 57.3 ± 16.3 years, and the mean duration from the initial onset of uveitis was 47.1 ± 22.1 months. Flare counts, ICGA scores, and subfoveal choroidal thickness (SFCT) were compared between eyes. Results . Although clinical ocular inflammation was observed only in 4 eyes (11.8%), inflammatory signs were observed in 23 out of 34 eyes by LFP (67.6%), in 27 eyes by ICGA (79.4%), and in 10 eyes by SFCT (29.4%). Active inflammatory signs detected by ICGA were observed in 77.8% by LFP and in 25.9% by SFCT. The strength of agreement (Cohen's kappa coefficient) between positive ICGA score and positive flare score was 0.406 (95% CI: 0.076–0.7359, P < 0.01 ), but there was no association between positive ICGA score and increased SFCT. In addition, positive flare count was the significant prognostic factor of positive ICGA score with odds ratio 11.7. Conclusions . Subclinical ocular inflammation signs were detected in most VKH patients with SGF by ICGA and a substantial proportion of which were also detected by LFP, whereas SFCT was less sensitive to detect subclinical inflammation.